Pharmacological evidence for a metabotropic glutamate receptor heterodimer in neuronal cells - David Moreno Delgado; Thor C Møller; Jeanne Ster; Jesús Giraldo; Damien Maurel; Xavier Rovira; Pauline Scholler; Jurriaan M Zwier; Julie Perroy; Thierry Durroux; Eric Trinquet; Laurent Prezeau; et al. (eLife, 2017)
Metabotropic glutamate receptors (mGluRs) are mandatory dimers playing important roles in regulating CNS function. Although assumed to form exclusive homodimers, 16 possible heterodimeric mGluRs have been proposed but their existence in native cells remains elusive. Here, we set up two assays to specifically identify the pharmacological properties of rat mGlu heterodimers composed of mGlu2 and 4 subunits. We used either a heterodimer-specific conformational LRET-based biosensor or a system that guarantees the cell surface targeting of the heterodimer only. We identified mGlu2-4 specific pharmacological fingerprints that were also observed in a neuronal cell line and in lateral perforant path terminals naturally expressing mGlu2 and mGlu4. These results bring strong evidence for the existence of mGlu2-4 heterodimers in native cells. In addition to reporting a general approach to characterize heterodimeric mGluRs, our study opens new avenues to understanding the pathophysiological roles of mGlu heterodimers.